The Search for Biomarkers to Aid in Diagnosis, Differentiation, and Prognosis of Childhood Idiopathic Nephrotic Syndrome - Stone, Hillarey; Magella, Bliss; Bennett, Michael R. (Frontiers in Pediatrics, 2019)
Identification of genes associated with childhood-onset nephrotic syndrome has significantly advanced our understanding of the pathogenesis of this complex disease over the past two decades, however the precise etiology in many cases remains unclear. At this time, we still rely on invasive kidney biopsy to determine the underlying cause of nephrotic syndrome in adults. In children, response to steroid therapy has been shown to be the best indicator of prognosis, and therefore all children are treated initially with corticosteroids. Because this strategy exposes a large number of children to the toxicities of steroids without providing any benefit, many researchers have sought to find a marker that could predict a patient’s response to steroids at the time of diagnosis. Additionally, the identification of such a marker could provide prognostic information about a patient’s response to medications, progression to end stage renal disease, and risk of disease recurrence following transplantation. Major advances have been made in understanding how genetic biomarkers can be used to predict a patient’s response to therapies and disease course, especially after transplantation. Research attempting to identify urine- and serum-based biomarkers which could be used for the diagnosis, differentiation, and prognosis of nephrotic syndrome has become an area of emphasis. In this review, we explore the most exciting biomarkers and their potential clinical applications.